2017
DOI: 10.1017/etds.2017.3
|View full text |Cite
|
Sign up to set email alerts
|

Constant slope maps on the extended real line

Abstract: Abstract. For a transitive countably piecewise monotone Markov interval map we consider the question whether there exists a conjugate map of constant slope. The answer varies depending on whether the map is continuous or only piecewise continuous, whether it is mixing or not, what slope we consider, and whether the conjugate map is defined on a bounded interval, half-line or the whole real line (with the infinities included).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…This implies that the map T a(0) is strongly recurrent hence by Theorems 5 and 8 also linearizable for any ℓ. [15] observed that the map T a(1) is not conjugate to any map of constant slope. It can be shown that for each choice of a sequence a = (a n ) n≥1 such that the corresponding T has finite topological entropy the following dichotomy is true: either T is recurrent and then equation (5) has no λ-solution for λ > e h(T ) , or T is transient and then equation (5) does not have any λ-solution.…”
Section: 2mentioning
confidence: 89%
“…This implies that the map T a(0) is strongly recurrent hence by Theorems 5 and 8 also linearizable for any ℓ. [15] observed that the map T a(1) is not conjugate to any map of constant slope. It can be shown that for each choice of a sequence a = (a n ) n≥1 such that the corresponding T has finite topological entropy the following dichotomy is true: either T is recurrent and then equation (5) has no λ-solution for λ > e h(T ) , or T is transient and then equation (5) does not have any λ-solution.…”
Section: 2mentioning
confidence: 89%
“…It is enough to construct a countably affine graph G of infinite total length and a constant slope map f ∈ CMM(G), whose transition matrix M has no summable eigenvectors. This was done in [15] on the extended real line [−∞, ∞].…”
Section: Discussion and An Open Questionmentioning
confidence: 99%
“…It is enough to construct a metric tame graph G of infinite total length and a constant-slope map f ∈ CMM(G) whose transition matrix M has no summable eigenvectors. This was done in [13] on the extended real line [−∞, ∞]. Note that the constant slope is with respect to the standard metric on R, which cannot be extended to [−∞, ∞], so to fit the example to our setting we formally realize [−∞, ∞] as a double-infinite countable zig-zag in R 2 of infinite length.…”
Section: Realization In Rmentioning
confidence: 99%
See 2 more Smart Citations